Analysing Continuity of Care Implementation in the Midwifery-Led Care Model in Malang Regency - Fatmawati, Fatmawati; Maharani, Afniari; Silvani, Yulia; Dewi, Mustika; Sari, Ningrum Paramita; Windari, Era Nurisa; Ulfa, Mega (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
This study aims to explore the implementation of Continuity of Care (CoC) within the Midwifery Led Care (MLC) model in Malang Regency. The maternal and child health indicators remain a concern due to high maternal mortality rates, exacerbated by complications such as preeclampsia and hemorrhage. CoC has been recognized for its ability to improve maternal and neonatal health outcomes by providing consistent care through midwives. This qualitative research, using a phenomenological approach, involved in-depth interviews with 20 mothers (10 primipara, 10 multipara) who experienced MLC, supported by observations and secondary data. Results revealed that both primipara and multipara mothers valued continuous midwifery care, though their experiences varied based on parity. Primipara mothers generally required more information and support, while multipara mothers exhibited greater confidence in midwife-led care. Barriers such as limited access to health services in remote areas, a lack of trained midwives, and insufficient community education on the benefits of MLC were identified. Recommendations include enhancing midwife training, improving access to healthcare in rural regions, and increasing public awareness of CoC benefits. The findings emphasize the importance of expanding MLC and CoC models to reduce maternal and neonatal morbidity and mortality in underserved areas.